TO STUDY PROS AND CONS OF EXTERNAL AND INTERNAL RECRUITING PROCESS (International Journal of Food and Nutritional Sciences, 2022)
External recruiting has pros and cons. Recruiting outside talent boosts innovation and creativity by bringing new views and ideas. External applicants' specific talents and knowledge help diversify the workforce and improve the organization's capacity to solve complicated problems. External recruiting also reduces internal biases and power dynamics, making selection more objective. It also broadens the pool of applicants, giving the company access to unique skills and experiences. The negative is that advertising, interviewing, and onboarding new workers costs more. External personnel may take longer to adjust to the corporate culture and operational details, affecting early productivity. External recruiting may dampen morale among current workers who hoped for internal progress due to the uncertainty of how effectively external applicants would fit into the work environment. Internal recruiting has pros and cons. Promoting from within boosts morale by showing workers that their hard work and progress are acknowledged, creating loyalty. Internal hires are familiar with the company's culture, processes, and team dynamics, which speeds up onboarding. Internal applicants' performance histories provide vital insights into their skills and work ethic, helping make better recruiting selections. It eliminates external advertising, recruiting, and training costs, making it cost-effective. Internal promotions preserve the company's culture and give stability. Skills diversity may be a problem, limiting new insights and creative ways. Internal promotions may slow the flow of fresh ideas and industry best practises, slowing growth. Internal promotions may sometimes cause animosity among non-selected staff, impacting team relations. For internal recruiting to work, familiarity must be balanced with skill shortages and restricted variety.